N‐Boc‐Protected α‐Amino Acids by 1,3‐Migratory Nitrene C(sp3)−H Insertion - Zhou, Bing; Ye, Chen‐Xi; Meggers, Eric (European journal of organic chemistry, 2023)
N‐Boc‐protected α‐amino acids are synthesized in two steps from linear or branched carboxylic acid feedstocks. In the first step, the carboxylic acid is coupled with tert‐butyl aminocarbonate (BocNHOH) to generate azanyl ester (acyloxycarbamate) RCO2NHBoc. In the second step, this azanyl ester undergoes a stereocontrolled iron‐catalyzed 1,3‐nitrogen migration to generate the N‐Boc‐protected non‐racemic α‐amino acid. This straightforward protocol is applicable to the catalytic asymmetric synthesis of α‐monosubstituted α‐amino acids with aryl, alkenyl, and alkyl side chains. Furthermore, α,α‐disubstituted α‐amino acids are accessible in an enantioconvergent fashion from racemic carboxylic acids. The new method is also advantageous for the synthesis of α‐deuterated α‐amino acids. N‐Boc‐protected α‐amino acids synthesized using this two‐step protocol are ready‐to‐use building blocks. A straightforward two‐step protocol was developed to convert linear or α‐branched carboxylic acids into non‐racemic N‐Boc‐protected α‐monosubstituted (asymmetric catalysis) or α,α‐disubstituted (enantioconvergent catalysis) α‐amino acids.